An Analysis of Twitter and Facebook Use by the Archival Community - Crymble, Adam (Archivaria, 2010)
This paper discusses how the archival community is using social networking services such as Twitter and Facebook as outreach tools. The study analyzes the usage patterns of 195 individual and institutional users over a thirty-two-day period during the summer of 2009. By focusing on the 2,926 outbound links posted to the services during the period, the author shows that use is dramatically different between the three test groups: archival organizations using Facebook, archival organizations using Twitter, and archivists using Twitter. The study shows that archival organizations overwhelmingly use the services to promote content they have created themselves, whereas archivists promote information they find useful. In all cases, more frequent posting did not correlate to a larger audience. By examining how others have applied social networking, archivists and archival organizations can determine a social media outreach platform that is suitable to their institutional needs. This study may serve as a starting point toward a greater understanding of outreach in the digital age. RÉSUMÉ Ce texte examine comment la communauté archivistique se sert des services de réseautage social, tels Twitter et Facebook, comme outils de rayonnement. L’étude analyse les modèles d’utilisation de 195 individus et institutions durant une période de trente-deux jours au courant de l’été 2009. En se concentrant sur 2 926 liens publiés sur ces sites pendant la période, l’auteur montre que l’usage est considérablement différent entre les trois groupes témoins : les institutions d’archives qui utilisent Facebook, les institutions d’archives qui utilisent Twitter et les archivistes qui utilisent Twitter. L’étude montre que les institutions d’archives se servent de ces sites en très grande majorité pour promouvoir le contenu qu’elles ont créé elles-mêmes, alors que les archivistes promeuvent l’information qu’ils trouvent utile. Dans tous les cas, il n’y a pas de corrélation entre la fréquence des publications et un plus grand public. En examinant comment les autres se sont servis des outils de réseautage social, les archivistes et les institutions d’archives peuvent arriver à déterminer la plateforme de réseautage social pour fins de rayonnement qui rencontre leurs propres besoins institutionnels. Cette étude peut servir de point de départ pour une plus grande compréhension du rayonnement à l’ère du numérique.